Implementasi Teknologi Tepat Guna Untuk Meningkatkan Kualitas dan Kapasitas Produksi Jamur Tiram di Probolinggo - Nourma Ulva Kumala Devi; Linda Kurnia Supraptiningsih; Retno Sulistiyowati; Aissatun Nafisah; Irgy Marchello; Veronica Sri Astuti Nawangsih (Fakultas Teknik, Universitas PGRI Banyuwangi, 2026)
The issues faced by partners in this activity include the ineffectiveness and inefficiency of the methods used in producing baglogs, both in the process of mixing wood powder and in baglog pressing, resulting in inconsistent baglog quality. The implementation of appropriate technology in the form of automatic mixing and automatic baglog pressing machines has successfully improved the quality and production capacity of oyster mushroom entrepreneurs in Ngepung Village, Probolinggo Regency. The partner for this Community Service activity is the Bromo Mandiri KTI Cooperative. The applied technology replaces manual methods for mixing wood powder and pressing baglogs, thereby increasing production efficiency by 4 to 5 times compared to manual methods, while producing baglogs with more uniform quality and higher resistance to contamination. Additionally, e-financial training was provided to the partners to enhance their financial management skills, enabling them to record transactions more neatly, manage cash flow effectively, and prepare simple financial reports that can serve as a basis for business decision-making.